De bedrieglijke verlokking van de tropen: Het vreemde in het dagboek van István Radnai - Pusztai, Gábor (Acta Neerlandica, 2015)
István Radnai left his home country in 1914, hoping to achieve a brighter and richer future life. With his cousin, László Székely, he traveled to the then Dutch Indies, to Sumatra in order to become rich as a planter. After five weeks, however, he returned disappointed to Hungary, where he saw the beginning of the First World War. On the basis of his diary it is possible to reconstruct the reasons why he found it necessary to escape from the “self” and why he chose the tempting, unknown world. The binary opposition formed in this way undergoes a change in a different context; it becomes shifted and turned around. The interesting “other” becomes frightful and threatening which makes the “self” more valuable at the same time.